Anodization-based process for the fabrication of all niobium nitride Josephson junction structures - Massimiliano Lucci; Ivano Ottaviani; Matteo Cirillo; Fabio De Matteis; Roberto Francini; Vittorio Merlo; Ivan Davoli (Beilstein Journal of Nanotechnology, 2017)
We studied the growth and oxidation of niobium nitride (NbN) films that we used to fabricate superconductive tunnel junctions. The thin films were deposited by dc reactive magnetron sputtering using a mixture of argon and nitrogen. The process parameters were optimized by monitoring the plasma with an optical spectroscopy technique. This technique allowed us to obtain NbN as well as good quality AlN films and both were used to obtain NbN/AlN/NbN trilayers. Lift-off lithography and selective anodization of the NbN films were used, respectively, to define the main trilayer geometry and/or to separate electrically, different areas of the trilayers. The anodized films were characterized by using Auger spectroscopy to analyze compounds formed on the surface and by means of a nano-indenter in order to investigate its mechanical and adhesion properties. The transport properties of NbN/AlN/NbN Josephson junctions obtained as a result of the above described fabrication process were measured in liquid helium at 4.2 K.